Technology in the Study of Production of Islamic Financial Institution Services at Bank Muamalat - Saifudin Saifudin (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
Financial technology is innovation related to financial services and technology, in which there are new applications, processes or models that aim to make it easier for society. The birth of this innovation made people's ability to be able to relate, especially in terms of transactions that were originally traditional to become modern or often called online. This study aims to determine the strengths, weaknesses, opportunities and threats of financial technology for banks in Indonesia at Bank Muamalat.This type of research is descriptive qualitative research with the SWOT analysis method. Data collection was carried out using the method of literature study and documentation. The data source used is a secondary data source from the official website of Bank Muamalat obtained from information technology management reports published in 2020. The data analysis technique used is data reduction, data presentation and drawing conclusions.Based on the research conducted, it is known that there are 4 analyzes, namely the strengths of financial technology, weaknesses in financial technology, opportunities in financial technology and threats to financial technology at Bank Muamalat. By looking at these four factors, there is a strategy especially for Bank Muamalat to increase market share and income.